Auditory P300 in individuals with high schizotypy: associations of schizotypal traits with amplitude and latency under different oddball conditions - Deng, Jue; Chen, Siwei; Ou, Yuanhua; Zhang, Yuanjun; Lin, Ziyue; Shen, Yane; Ye, Yiduo (Frontiers in Human Neuroscience, 2023)
Background The aim of this study was to compare the characteristics of auditory P300 between non-clinical individuals with high and low schizotypal traits, and investigate the relationship between schizotypy and P300 under various oddball conditions. Methods An extreme-group design was adopted. After screening 1,519 young adults using the Schizotypal Personality Questionnaire (SPQ), sixty-three participants were chosen and divided into two groups (schizotypy group: 31 participants; control group: 32 participants). Basic demographic information was assessed and matched between groups. Depression and anxiety indexes were evaluated and controlled. The P300 component was evoked by an auditory oddball paradigm with different frequencies and durations. Results (1) The duration P300 amplitude at PZ site was significantly weaker in the schizotypy group than in the control group [F(1,54) = 7.455, p = 0.009, ηp2 = 0.121]. (2) In the schizotypy group, the latency of frequency P300 at PZ site under large-variant oddball condition was significantly correlated with total SPQ scores (rp = 0.451, p = 0.018) and disorganized dimension scores (rp = 0.381, p = 0.050). (3) In the control group, significantly negative correlations was found between the negative dimension score of SPQ and the frequency P300 amplitudes under small variant condition (PZ: rp = −0.393, p = 0.043; CPZ: rp = −0.406, p = 0.035). In addition, a significant negative relationship was found between disorganized dimension scores and the duration P300 latency at CPZ site under large-variant oddball condition (rp = −0.518, p = 0.006). Moreover, a significant negative association was found between the duration P300 amplitude at CPZ site under small-variant oddball condition and negative factor scores (rp = −0.410, p = 0.034). Conclusion Individuals with high schizotypal traits were likely to have deficient attention and hypoactive working memory for processing auditory information, especially the duration of sounds. P300 effects were correlated with negative and disorganized schizotypy, rather than positive schizotypy. There were diverse patterns of relationship between schizotypal traits and P300 under different oddball conditions, suggesting that characteristics and parameters of target stimuli should be considered cautiously when implementing an auditory oddball paradigm for individuals with schizophrenia spectrum.